Immunoprotection of mice against Schistosomiasis mansoni using solubilized membrane antigens. - Guidenn Sulbarán; Oscar Noya; Beatríz Brito; Diana E Ballén; Italo M Cesari (PLoS Neglected Tropical Diseases)
Background Schistosomiasis continues to be one of the most prevalent parasitic diseases in the world. Despite the existence of a highly effective antischistosome drug, the disease is spreading into new areas, and national control programs do not arrive to complete their tasks particularly in low endemic areas. The availability of a vaccine could represent an additional component to chemotherapy. Experimental vaccination studies are however necessary to identify parasite molecules that would serve as vaccine candidates. In the present work, C57BL/6 female mice were subcutaneously immunized with an n-butanol extract of the adult worm particulate membranous fraction (AWBE) and its protective effect against a S. mansoni challenge infection was evaluated. Methodology and findings Water-saturated n-butanol release into the aqueous phase a set of membrane-associated (glyco)proteins that are variably recognized by antibodies in schistosome-infected patients; among the previously identified AWBE antigens there is Alkaline Phosphatase (SmAP) which has been associated with resistance to the infection in mice. As compared to control, a significantly lower number of perfuse parasites was obtained in the immunized/challenged mouse group (P<0.05, t test); and consequently, a lower number of eggs and granulomas (with reduced sizes), overall decreasing pathology. Immunized mice produced high levels of sera anti-AWBE IgG recognizing antigens of ∼190-, 130-, 98-, 47-, 28-23, 14-, and 9-kDa. The ∼130-kDa band (the AP dimer) exhibited in situ SmAP activity after addition of AP substrate and the activity was not apparently inhibited by host antibodies. A preliminary proteomic analysis of the 25-, 27-, and 28-kDa bands in the immunodominant 28-23 kDa region suggested that they are composed of actin. Conclusions Immunization with AWBE induced the production of specific antibodies to various adult worm membrane molecules (including AP) and a partial (43%) protection against a challenging S. mansoni infection by mechanism(s) that still has to be elucidated.